Experimental analysis of indoor air quality for human comfort in vehicle cabin / Siti Nor' Ain Mokhtar - Siti Nor'Ain, Mokhtar (2021)
In present time more people spend a relatively longer time inside their vehicles. However, the microenvironment of a vehicle cabin is vulnerable to exposure of air contaminants such as carbon dioxide, Carbon Dioxide (CO2) and Particulate Matter PM10 originated from the surrounding and vehicle operation. Carbon Dioxide would cause acidosis, which is particularly harmful to the cells of the brain. Even at low-to-moderate, CO2 (>800ppm) has been found to be associated with headache, fatigue, kidney failure and reduce cognitive ability in humans. Exposure to Particulate Matter10 affects the lungs and heart, leading to health complication such as nonfatal heart attacks, irregular heartbeat, aggravated asthma, decreased lung function, and increased respiratory symptoms. The purpose of this study is to assess and analyze the indoor air quality Indoor Air Quality (IAQ) of a car travelling the route between UTeM main campus and FTK campus. This experiment was conducted for Perodua Myvi and Honda Freed for 2 condition of time there is morning and evening. The assessment was conducted in a car as it was travelling along the designated route. Total route of 2 destination are16km. The 3M EVM (Environmental Monitor) was set up to measure the parameters such as temperature, carbon dioxide (CO2), and particulate matter (PM10). Additionally, the study regarding the number of passengers and vehicle operation (driving/idling) was also done. The average temperature for Perodua Myvi during morning was 26.9°C, while 27.0°C for evening which staying within the DOSH acceptable range, 26-27.0°C. Whereas the average temperature for Honda Freed during morning and evening was 27.3°C and 27.5°C respectively which exceed than Department of Safety and Health (OSH) acceptable range. The overall mean of CO2 concentration for Perodua Myvi during morning for 2 and 5 passengers are 276 and 291 respectively. While during evening are 114 and 196 respectively. Honda Freed is gradually increase during evening up to 627 for 5 passengers compared with Perodua Myvi. In term of Particulate Matter, the experimental data for both cars during morning and evening are within acceptable range of 150μg/m3 from United States Environmental Protection Agency (USEPA).